Antioxidant Activity of Cinnamon Bark Oil (Cinnamomum zeylanicum L.) in Japanese Quails Under Thermo Neutral and Heat Stressed Conditions - Simsek, Ulku Gulcihan; Ciftci, Mehmet; Dogan, Gulden; Ozcelik, Mehtap (Kafkas Univ, Veteriner Fakultesi Dergisi, 2013)
The essential oil from bark of Cinnamomum zeylanicum Lauraceae was analyzed by GC and GC-MS systems in this research. The essential oil was obtained by hydrodistillation, in 0.7 (v/w) oil yields. Twelve constituents representing 99.2% of the cinnamon oil were identified. The major compounds in the oil were cinnamaldehyde (88.2%), benzyl alcohol (8.0%) and eugenol (1.0%). To determine antioxidant activity of the cinnamon oil, a total of 180 quails, fifteen-days-old, were allocated into 6 groups consisting of 10 birds of 3 replicates according to balanced gender and inital live weight. The birds were kept in wire cages in a temperature controlled room at 22 degrees C for 24 h/d in thermo-neutral (TN) groups. For heat-stress (HS) groups, the birds were exposed to 34 degrees C for 8 h/d (from 9: 00 to 17: 00), and later 22 degrees C 16 h/d was performed. Relative humidity was approximately 60-65%. Basal diet was given to control groups in both TN and HS. The birds were fed with the basal diet supplemented 250 or 500 ppm cinnamon oil in the other experimental groups. Heat stress increased the malondialdehyde (MDA) levels of liver (P<0.001), heart (P<0.01) and kidney (P<0.05). It also induced superoxide dismutase (SOD) production of liver (P<0.001) and kidney (P<0.05). Glutathione peroxidase (GSH-Px) activity and glutathione (GSH) level of liver (P<0.001, P<0.05) and heart (P<0.001, P<0.05) were found lower under HS condition. Cinnamon oil supplementation to diet significantly increased antioxidant enzyme activity and GSH level of the tissues in both enviromental conditions (P<0.01). Dose of 500 ppm cinnamon oil had strong effect on antioxidant activity of the internal organs (P<0.01). In conclusion, cinnamon oil supplementation to diet reduced the adverse effects of heat stress and resulted the protective effect on the internal organs by activating antioxidant mechanism.
Termo-nötral ve sıcaklık stresi koşullarındaki japon bıldırcınlarında tarçın kabu?u ya?ının (Cinnamomum zeylanicum L.) antioksidan aktivitesi
Keywords: GC-MS; Cinnamon oil; Lipid peroxidation; Antioxidant activity; Quail; Heat stress